Prevalence and incidence of diabetes among Aboriginal people in remote communities of the Northern Territory, Australia: a retrospective, longitudinal data-linkage study. Issue 5 (15th May 2022) - Hare, Matthew J L; Zhao, Yuejen; Guthridge, Steven; Burgess, Paul; Barr, Elizabeth L M; Ellis, Elna; Butler, Deborah; Rosser, Amy; Falhammar, Henrik; Maple-Brown, Louise J
Abstract : Objectives: To assess the prevalence and incidence of diabetes among Aboriginal peoples in remote communities of the Northern Territory (NT), Australia. Design: Retrospective cohort analysis of linked clinical and administrative data sets from 1 July 2012 to 30 June 2019. Setting: Remote health centres using the NT Government Primary Care Information System (51 out of a total of 84 remote health centres in the NT). Participants: All Aboriginal clients residing in remote communities serviced by these health centres (N=21 267). Primary outcome measures: Diabetes diagnoses were established using hospital and primary care coding, biochemistry and prescription data. Results: Diabetes prevalence across all ages increased from 14.4% (95% CI: 13.9% to 14.9%) to 17.0% (95% CI: 16.5% to 17.5%) over 7 years. Among adults (≥20 years), the 2018/2019 diabetes prevalence was 28.6% (95% CI: 27.8% to 29.4%), being higher in Central Australia (39.5%, 95% CI: 37.8% to 41.1%) compared with the Top End region (24.2%, 95% CI: 23.3% to 25.1%, p<0.001). Between 2016/2017 and 2018/2019, diabetes incidence across all ages was 7.9 per 1000 person-years (95% CI: 7.3 to 8.7 per 1000 person-years). The adult incidence of diabetes was 12.6 per 1000 person-years (95% CI: 11.5 to 13.8 per 1000 person-years). Conclusions: The burden of diabetes in the remote Aboriginal population of the NT is among the highest in the world. Strengthened systems of care and public health prevention strategies, developed in partnership with Aboriginal communities, are needed.